The relationship between board value and corporate performance in Bursa Malaysia Ace Market / Muhammad Umar Kamarol Anhar - Anhar, Muhammad Umar Kamarol (Faculty of Business and Management, 2018)
Corporate performance is one of the method of companies and investor use to identify the condition of the company. Many previous researcher have been made several studies to find the factor that cause of fluctuation of corporate performance in many type of sector which lead to many different results. In this study, I aim to identify the effect of board value toward corporate performance. The board value that I attempt to use in this study is board gender diversifies and board independence. I use data from 35 companies listed in Bursa Malaysia ACE Market that being choose using simple random method. Period for the data is from year 2012-2017. The firm year observation is 210. I use panel data method to investigate the relationship between the dependent and independent variable. The company performance is fluctuate from year to year based on many factor. The company usually will monitor the financial condition such as leverage and equity to see their impacts toward corporate performance but the company not focusing the other factor that also can give the impact to corporate governance which is board value. A lot of companies being listed in the financial distress company because their failed to detect the real factor that can give impact to the corporate performance like board value. This study can be used to help the company, investors and future investors to reduce their risk and improving their investment strategy in future. Overall there is two variable that have significant relationship with corporate performance which is leverage and MCAP while other variable do not have significant relationship with corporate performance.